The architecture of psychoanalysis : spaces of transition - Rendell, Jane, 1967- (I.B. Tauris, 2016)
In this thought-provoking book, Jane Rendell explores how architectural space registers in psychoanalysis. She investigates both the inherently spatial vocabulary of psychoanalysis and ideas around the physical 'setting' of the psychoanalytic encounter, with reference to Sigmund Freud, D.W. Winnicott and Andre Green. Building on the innovative writing methods employed in Art and Architecture and Site-Writing, she also addresses the concept of architecture as 'social condenser' a Russian constructivist notion that connects material space and community relations. Tracing this idea's progress from 1920s Moscow to 1950s Britain, Rendell shows how interior and exterior meet in both psychoanalysis and architectural practice. Illuminating a novel field of interdisciplinary enquiry, this book breathes fresh life into notions of social space."